Cumulative selectivity benefits of increasing mesh size and using escape gaps in Australian Portunus armatus traps. (5th June 2019) - Broadhurst, Matt K.; Smith, Timothy M.; Millar, Russell B.; Hughes, Brian; Raoult, Vincent; Gaston, Troy F.
Abstract: The individual and cumulative effects of increasing mesh size (from 56‐ to 75‐mm stretched mesh opening) and installing three escape gaps (36 × 120 mm) in collapsible‐netted round traps were assessed to address concerns associated with excessive discarding in an Australian portunid fishery. Compared to conventional traps comprising 56‐mm mesh throughout, those with the same mesh size and escape gaps caught significantly fewer (by 54%) undersized blue swimmer crabs, Portunus armatus Milne‐Edwards and yellowfin bream, Acanthopagrus australis Günther (by 64%). Irrespective of escape gaps, simply increasing the mesh size to 75 mm did not significantly affect catches of undersized P. armatus, although 87% fewer A. australis were retained. Traps with both 75‐mm mesh and escape gaps maintained reductions of A. australis, but had a clear cumulative effect on P. armatus selection, retaining 84% fewer undersized individuals across a larger size at retention. The results support using escape gaps in existing conventional traps, but illustrate the need to configure the minimum legal mesh size to approach the desired target size of P. armatus as a precursor to maximising trap selectivity. Larger‐meshed traps also require less material (i.e. plastic), which benefits their manufacture and, equally importantly, reduces environmental costs when lost.